2018
DOI: 10.1016/j.celrep.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A NuRD Complex from Xenopus laevis Eggs Is Essential for DNA Replication during Early Embryogenesis

Abstract: SummaryDNA replication in the embryo of Xenopus laevis changes dramatically at the mid-blastula transition (MBT), with Y RNA-independent random initiation switching to Y RNA-dependent initiation at specific origins. Here, we identify xNuRD, an MTA2-containing assemblage of the nucleosome remodeling and histone deacetylation complex NuRD, as an essential factor in pre-MBT Xenopus embryos that overcomes a functional requirement for Y RNAs during DNA replication. Human NuRD complexes have a different subunit comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…It has been suggested that gene regulatory complexes such as the COMPASS , PRC2 and the BAP1 complexes can play cytoplasmic roles. Indeed, enzymatically active subcomplexes of NuRD have also been observed in the cytosol . However, SLC25A5 has also been convincingly shown to be present in the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that gene regulatory complexes such as the COMPASS , PRC2 and the BAP1 complexes can play cytoplasmic roles. Indeed, enzymatically active subcomplexes of NuRD have also been observed in the cytosol . However, SLC25A5 has also been convincingly shown to be present in the nucleus .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this model it has been shown, though at only one stage post-MBT, that overexpression of four replication initiation factors (Treslin, RecQ4, Drf1, TopBP1) delays the onset of the MBT in Xenopus laevis and reduces replication track distances [21]. Other factors such as protein phosphatase 2A [22], non-coding Y RNAs [23], the chromatin remodeling complex xNuRD [24], histones [25], Rap1 interacting factor (Rif1) [26] and dNTP pools have also been linked to the change of DNA replication program or the DNA:cytoplasm ratio at the MBT. Injection of dNTPs into early embryos leads to extra cleavage cycles [27], and early embryos treated with the ribonucleotide reductase (RNR) inhibitor hydroxyurea (HU) are arrested at the MBT [28].…”
Section: Introductionmentioning
confidence: 91%
“…Recently, a requirement for early cleavages DNA replication of a large chromatin remodeling complex xNuRD, has been highlighted in early Xenopus embryos. Before MBT, this complex seems to ensure the function of small non coding Y-RNAs in replication initiation observed after MBT [21,22], however the molecular mechanism involved remains currently unclear [23]. Furthermore, while Y-RNAs function appears to be conserved in somatic human cells, NuRD activity is not shared.…”
Section: Embryonic Dna Replicationmentioning
confidence: 99%